2021
DOI: 10.3390/ani11010215
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Reduces Metabolic Rate While Increasing Respiratory Exchange Ratio in Growing Pigs

Abstract: Heat stress (HS) diminishes animal production, reducing muscle growth and increasing adiposity, especially in swine. Excess heat creates a metabolic phenotype with limited lipid oxidation that relies on aerobic and anaerobic glycolysis as a predominant means of energy production, potentially reducing metabolic rate. To evaluate the effects of HS on substrate utilization and energy expenditure, crossbred barrows (15.2 ± 2.4 kg) were acclimatized for 5 days (22 °C), then treated with 5 days of TN (thermal neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…However, our results suggest otherwise-although such losses did not significantly affect all the studied parameters. Acute and chronic HS reduces metabolic rate, causes metabolism disorders, acute phase response, and respiratory alkalosis that might affect the electrolyte balance of pigs [11,[46][47][48]. The concentration of plasma Cl − obtained from pigs under HS + fed basal diet (HC) was significantly reduced (p < 0.01) and is below the reference range in pigs (94-106 mmol/l) [49], regardless of the duration of exposure, which is in contrast to the results observed by Pearce et al [5] in pigs exposed to acute HS (2-6 h).…”
Section: Discussionmentioning
confidence: 99%
“…However, our results suggest otherwise-although such losses did not significantly affect all the studied parameters. Acute and chronic HS reduces metabolic rate, causes metabolism disorders, acute phase response, and respiratory alkalosis that might affect the electrolyte balance of pigs [11,[46][47][48]. The concentration of plasma Cl − obtained from pigs under HS + fed basal diet (HC) was significantly reduced (p < 0.01) and is below the reference range in pigs (94-106 mmol/l) [49], regardless of the duration of exposure, which is in contrast to the results observed by Pearce et al [5] in pigs exposed to acute HS (2-6 h).…”
Section: Discussionmentioning
confidence: 99%
“…Pigs are highly susceptible to HS because of their scattered sweat glands and elevated metabolic rate [ 2 ]. The negative impact of HS on pig growth has been shown in cosmopolitan pigs [ 3 ] and also in purebred Iberian pigs [ 4 ]. The exact mechanisms of heat stress-induced reactions in productivity are unknown but might be partially mediated by its effects on intestinal integrity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that heat stress plays a negative role in animal welfare and animal production, especially in broilers (Soravia et al, 2021). During heat stress, energy metabolism is reduced, leading to poor organ development and decreased mass gain (Fausnacht et al, 2021). It has been reported that energy metabolism and immunity are related (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%